Gambaran Personal Hygiene Berdasarkan Persepsi Pola Asuh Anak di UPTD Kampung Anak Negeri - Riana Bintang Rozaaqi (Poltekkes Kemenkes Surabaya, 2017)
Personal hygiene is one of health problems that suffered by children. Lack care of personal hygiene can cause some health problems such as skin and digestive tract disease such as diarrhea, worms, scabies, and others. Parenting has big contribution on the personal hygiene behaviour. This research is descriptive research with quantitave and qualitative approach. Based on the time it is the cross sectional reasearch. The sample was 30 respondent for questionnaires and 7 informant for indepth interview, with determining the sample with purposing sampling. Data was taking with questionnaires and indepth interview. Intrument that used in this research was questionnaires and indepth interview guidance. Data analysis was conducted with cross tabulation analysis. The results is most of the respondents were 12-16 years old. Most of the respondent were in the road more than 7 months. The majority of respondent were schoolless. Most of the respondents enter the UPTD because singing in the road. Most of the respondents have a good personal hygiene. Most of the respondent have democratic perception on parenting. The conclusion of this research is respondents that have otoriter, democratic, as well as permissive perception on parenting have good perception on personal hygiene.